Environmental impact assessment of a graphic company that uses offset lithographic printing - Villalobos-González, Wendy (2021)
The graphic industry is dedicated to printing documents using different technologies, one of which being offset lithographic printing. This production process and the use of chemical substances generate a negative environmental impact. The purpose of this environmental impact assessment (EIA) is to identify and evaluate the environmental impact and generate preventive, corrective, and compensatory measures. Generally, the main effects of this type of industry include generation of wastewater, gas emissions, noise, and solid waste. This research identified, assessed, and prioritized the main environmental aspects (AAs) and environmental impacts (IAs) generated in the offset lithographic industry in Costa Rica. Physicochemical analyses of wastewater (AR), volatile organic compounds (VOCs), total suspended particles (TSPs), noise, and luminosity were conducted to know the environmental situation of the industry. Environmental aspects were identified in conjunction with company officials, environmental management experts and through work sessions with focus groups, using tools such as bibliographic reviews, checklists, interviews and field inspections. The environmental aspects identified were assessed and prioritized using the Matrix of Environmental Impact Importance (MIIA) methodology. A total of 16 environmental aspects and 5 environmental impacts were identified. The most critical negative environmental aspect is VOC emissions, mainly due to the high concentrations found in the internal production plant and inefficient general or localized extraction systems. The three main negative environmental impacts were air pollution, health effects, and depletion of non-renewable resources, with environmental impact values of -64, -62 and -62, respectively.